BANDIERI, S., MÉNDEZ, L., PIANTONI, G., PIERUCCI, L. y MORALES, M. (2021). Río Negro. Los caminos de la Historia. Neuquén: Pido la Palabra, 311 páginas (tomo 1) y 425 páginas (tomo 2). - Arancibia Agüero, Luciano (Revista Paginas, 2022)
.